Bilingual Children Socialization in Galicia: Conversational Sequences of Call for Attention in an Early Childhood Education Classroom - Díaz-Ferro, Marta (Madrygal. Revista de Estudios Gallegos, 2019)
This paper refers on bilingual child socialization in a classroom of early childhood education in the city of Vigo (Galicia), mainly a Spanish-speaking area; the 25 children in this classroom receive a great input in Galician language, the basic code used by the teacher, with code switching to Spanish. This article is focus on a group of conversational sequences that take place during one of the most important routines of the school day, known as Tempo de asemblea; the importance of this session lies in the literacy and organization tasks conducted during it. Among these tasks, this paper concentrates on a series of interactions named calls to attention from the teacher to the children. The aim of this paper is to analyse those sequences and check the different uses the teacher made of them, what functions she attributes them depending on the different situations arising during the school day. The results point out there is a decrease in this type of interaction due to the positive evolution in the children’s behaviour: they grow up, and they learn how to internalize the behavioural patterns required at every moment of the school day, specifically during this Tempo de asemblea.
Keywords: Socialization; Child Bilingualism; School; Attention Calls; Interactional Ethnography